Sustained delivery of PlGF-2123-144*-fused BMP2-related peptide P28 from small intestinal submucosa/polylactic acid scaffold material for bone tissue regeneration. Issue 12 (19th February 2020) - Xiong, Zekang; Cui, Wei; Sun, Tingfang; Teng, Yu; Qu, Yanzhen; Yang, Liang; Zhou, Jinge; Chen, Kaifang; Yao, Sheng; Shao, Zengwu; Guo, Xiaodong
Abstract : Sustained delivery of PlGF-2123-144* -fused BMP2-related peptide P28 from SIS/PLA scaffold facilitate the adhesion, proliferation, and osteogenic differentiation of bone marrow stromal cells. This system effectively promotes segmental bone repair. Abstract : Bone morphogenetic protein 2 (BMP-2) is one of the most important factors for bone tissue formation. However, its use over the past decade has been associated with numerous side effects. This is due to the fact that recombinant human (rh) BMP-2 has several biological functions, as well as that non-physiological high dosages were commonly administered. In this study, we synthesized a novel BMP-2-related peptide (designated P28) and fused a mutant domain in placenta growth factor-2 (PlGF-2123-144* ) that allowed for the "super-affinity" of extracellular matrix proteins to P28, effectively controlling the release of low dosage P28 from small intestinal submucosa/polylactic acid (SIS/PLA) scaffolds. These have been shown to be excellent scaffold materials both in vivo and in vitro . The aim of this study was to determine whether these scaffolds could support the controlled release of P28 over time, and whether the composite materials could serve as structurally and functionally superior bone substitutes in vivo . Our results demonstrated that P28 could be released slowly from SIS/PLA to promote the adhesion, proliferation, and differentiation of bone marrow stromal cells (BMSCs) in vitro . In vivo, radiographic and histological examination showed that SIS/PLA/P28/PlGF-2123-144* completely repaired critical-size bone defects, compared to SIS/PLA, SIS/PLA/PlGF-2123-144*, or SIS/PLA/P28 alone. These findings suggest that this controlled release system may have promising clinical applications in bone tissue engineering.